The Effect of Grammar Teaching Methods on Structure Assignments in Physiotherapy Students - Noerdjanah, Noerdjanah; Sugiono, Sugiono; Khomarun, Khomarun; Mutaqin, Wawan Ridwan (UIN Sultan Aji Muhammad Idris Samarinda, 2024)
Good English language skills are a much-needed skill in today's market share. The Physiotherapy study program also has a high awareness in responding to the importance of English language skills in the current era. Thus, the Physiotherapy study program provides courses that support students' English language skills. The courses are English Physiotherapy and English Conversation. However, 55% of students of the class of 2023 have a pre-test score below the criteria, which is 65. This indicates that the English language skills of Physiotherapy students are still low. This study aims to determine the influence of grammar teaching methods on structural assignments. The design used is the